Experimental and Numerical Simulation Study on Shear Strength and Secondary Particle Breakage of Coarse Sand with Different Dry Densities - Rui Luo; Fangcai Zhu; Qing Liu; Shaolong Zhang; Binbin Wu; Yaxin Shang; Qi Chen (Geofluids)
In order to guarantee perpendicularity of rotary cast-in-place pile in Karst areas, filling, like sand, etc., is commonly used between the inner steel casing and the outer steel sleeve; while the outer steel sleeve is pulled out or a vertical load is applied on the top of the pile, the sand will move, contact, and push against each other, which leads to recrushing; therefore, shear characteristics and secondary breakage are a meaningful problem to study with regard to the influence of different sand densities. Through experimental direct shear tests, with different dry densities, shear stress versus shear displacement curves are obtained and internal friction angles are analyzed. The results show that internal friction angles increase along with increment of dry densities; more interesting is that the secondary breakage ratio also increases. A comparative numerical 2D model is set up using PFC2D, with lower porosity used to simulate a large dry density, and similar results are obtained, that is to say, with increase of dry densities, internal friction angles also increase.